Anglicisms in German – An Overview with Reference to the Neologismenwörterbuch in the Online-Wortschatz- Informationssystem Deutsch (OWID) - Cantarini, Sibilla (Neophilologica, 2023)
Neologisms indicate linguistic changes in the lexicon. Vocabulary is particularly prone to changes since language communities constantly need new words and phrases to denote new facts or circumstances or they require new expressions for concepts already established. New expressions are often borrowed from other languages. English has had a strong influence on German vocabulary in the last decades. Therefore, German has several English borrowings. These anglicisms differ in their degree of integration into the linguistic system and vary, for instance, with respect to usage, style, and diffusion in the language community. With the help of the Neologismenwörterbuch, it is possible to have an overview of neologisms of English origin in German that integrate different areas of language change.